(untitled) (EAAE Joint Publishings, 2026)
How do we teach thinking about systems in design studios? And, more importantly, how do we move systems beyond the building and into community relationships, environmental concerns, and social equity? Our food system is unbalanced and unjust; with the rising temperatures and climate crisis, our already uneven system is being pushed to its limits. This paper will be a case study centered around two fourth-year undergraduate studios. It will explore a pedagogical interdisciplinary approach to exploring the intersection of climate/environmental justice and food justice in the design studio. These studios will focus on three pedagogical approaches and themes: interdisciplinary studies, systems-level interventions, and climate realities. Through these three pedagogical approaches, students will develop an understanding of the building, not as an isolated formal exercise but as a contribution to existing communities. The key issues addressed are local food inequity, community, site, and environmental justice. These studio exercises build on ongoing university research exploring the intersection of urban research, pedagogy, and practice. Urban research has long been essential for understanding urban areas’ challenges and opportunities. Still, the gap between academic research and practical implementation remains challenging, especially in design. We will discuss how studios could be used as public research infrastructures and leveraged as a design tool for bridging this gap.